Serum Zinc Level in Patients with Heart Failure - Al-Hamwandi, Adnan M; Al-Dalla, Fakhri j; Mohammed, Hatem H; AL-Baldawi, Kadhim H.; AL-Baldawi, Kadhim H.; Diyaiy, Muna A (AL-Kindy College Medical Journal, 2006)
Background: Zinc is involved in a variety of metabolic processes and it has a well known antioxidant activity, so the measurement of its serum level can have a special value in several diseases. Objectives: The study is designed to determine the serum zinc level in heart failure patients and to compare it with that of healthy individuals and to study the significance of the results obtained. Methods: Atomic absorption spectrometer technique was used to determine serum zinc level in fifty heart failure patients and fifty healthy individuals who were age and sex matched. Results: The mean serum zinc level in healthy individuals was about 45.5% greater than that of heart failure patients. This difference was statistically significant. Conclusion: The reduced serum zinc level in heart failure patients could be an acceptable risk factor for the development and/or deterioration of heart failure and therefore its correction might have a positive effect on management and prognosis of such patients